Distance vector-hop range-free location algorithm for wireless sensor network - Zazali, Azyyati Adiah (2015)
Wireless Sensor Network (WSN) has become a significant technology that is attracting enormous research interest in the area of localization for sensor nodes. The localization algorithms for sensor nodes can be classified into three categories; range-based, rangefree and hybrid. These localization algorithms are used to measure the actual distances between nodes and eventually determine the respective locations. Distance Vector-Hop (DV-Hop) algorithm has become the focus of studies for range-free localization algorithms. However, existing works on DV-Hop localization algorithm held onto the assumption that the placement of sensor nodes has been pre-determined before they are being distributed. This has caused the tasks for each sensor node to be permanently fixed, thus causing the overall process of the localization algorithm to be complex. In addition, these works have limited the flooding process in localization to be mostly done either by manual configuration or through the Global Positioning System (GPS),both of which are used to estimate the position of the sensor nodes. This has caused a complexity in the algorithm, along with the infeasible usage of GPS in the flooding process which requires high power consumption and challenge the limited battery powered sensor nodes. Thus, this research has proposed two ideas. First is the intelligent nodes placement algorithm for sensor nodes in order to introduce algorithm with low complexity and low localization error. The second idea proposed is the improvement of the region area for sensor nodes placement to control the network flooding associated problems, whilst increasing the network lifetime, reduce power consumption and minimizing the localization error. Extensive Discrete Event Simulation (DES) experiments have been conducted to the DV-Hop localization algorithm as one of the typical representative of range-free localization algorithm for the purpose of performance analysis strategy. The process in DES based on the initialization, scheduler and events. During the events, the positioning process of the DV-Hop happened. The performance metrics for the first idea are the average localization error of the nodes and the event time for distribution of nodes inside the area while for the second idea, the average localization error also calculated. The other performance metrics are the power transmission of the nodes and the coordinate accuracy. The acquired results have proven that the proposed algorithms have successfully enhanced the DV-Hop localization algorithm with low complexity, and low localization error, increase the network lifetime and reduce the power consumption for a range-free localization algorithm.